Eksplorasi Fungi Endofit dari Tanaman Sambung Nyawa (Gynura procumbens (Lour.)Merr.) - Ranti; Ummi Hiras Habisukan; Amin Nurokhman (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Sambung nyawa (Gynura procumbens(Lour.) Merr.) is a plant that can be used as herbal medicine such as healing cuts, lowering blood sugar levels, facilitating menstruation, and preventing cancer formation. The various properties possessed by sambung nyawa plants make these plants continue to be used and experience plant scarcity. Another alternative is to use endophytic fungi which are known as a source of efficacious medicinal secondary metabolites but have not been widely used. This study aims to isolate and identify the genus of endophytic fungi on sambung nyawa plants. The method used in this study was sampling, namely root organs, root bark, stems and leaves of sambung nyawa plants, making media using instant PDA media mixed with aquadest and antibiotics, endophytic fungi using direct planting techniques on PDA media in cups. petri, purification of endophytic fungi by eliminating fungi that are considered to be the same from their morphological characteristics until truly pure fungi are found, endophytic fungi help macroscopically by observing the color, texture, and pattern of the colony then observing microscopically using the culture slide technique then observing under a hyrox microscope by observing the type of spore, spore shape and hyphae. The results of this study were 12 isolates of endophytic fungi identified in 10 different genera, namely Nigrospora, Blastomyces, Fusarium, Pythium, Cladosporium, Trichoderma, Gliocladium, Papulaspora, Aspergillus, Monacrosporium.